Asymptomatic Pulmonary Embolism After Shoulder Arthroscopy: Case Report and Literature Review. Issue 3 (14th March 2021) - Ji, Le; Lyu, Chang‐lei; Feng, Min; Qiang, Hui
Abstract : Background: Pulmonary embolism (PE) is extremely rare after shoulder arthroscopy. However, early identification of the situation deserves attention due to its potential risk of causing death. By now, it is still difficult to detect the PE without symptoms and clear sources during the perioperative period. Case presentation: We report here two cases of asymptomatic PE, both happening within 24 h after shoulder arthroscopy, without any detected deep venous thrombosis of extremities. It is suspected the cases were due to the abnormal decrease in partial pressures of oxygen and arterial oxygen saturation, and were confirmed by computed tomography pulmonary angiography. We also discuss the reason why the patients showed no related symptoms when PE occurred and perform a review of PE following shoulder arthroscopy. Conclusions: This report highlights that PE could occur in the early phase after shoulder arthroscopy. An unexplained decrease in partial pressure of oxygen or arterial oxygen saturation should be considered seriously. The symptoms of PE might be masked due to patients' tolerance to hypoxia. Abstract : Pulmonary embolism (PE) could occur in the early phase after shoulder arthroscopy. An unexplained decrease in partial pressure of oxygen or arterial oxygen saturation should be considered seriously. The symptoms of PE might be masked due to patients' tolerance to hypoxia.